Kebijakan Komunikasi dalam Membangun Masyarakat Sadar Wisata Di Kabupaten Bengkalis-Riau - Yasir, Yasir; Nurjanah, Nurjanah; Salam, Noor Efni; Yohana, Nova (Jurnal Studi Komunikasi, 2019)
Tourism development policies requires the active community participation. This study aims to understand the policy and communication tourism in developing community tourism awareness in Bengkalis Regency. The research method used in this study is a case study. The results show the tourism policy in Bengkalis Regency is based on the laws and regulations of the central government in synergy with the government of Riau Province. The communication tourism of government is done by forming and mobilising some groups in the community as tourism awareness groups. Tourism development requires good communication policy, because both have an inseparable relationship in building a sustainable tourist destination. The government should coordinate and evaluate all the communication activities regularly not only within the internal service of the government, but also carried out together with the stakeholders involved.